Analisis Pemikiran Umar bin Khattab Tentang Pengguguran Hak Muâ€™allaf sebagai Mustahiq Zakat - Syaifudin, Muhammad (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2012)
In the reign of Khulafaurrasyidin, the fourth caliph no longer provide theÂ right of muâ€™allaf to the beneficiary, relying on Umar who flatly refuse toÂ give alms to the rights of muâ€™allaf in the reign of Abu Bakr, and his reign. InÂ fact, since the time of the Prophet they continue to receive zakat. This isÂ where Omar issued a statement of law, that the al-muâ€™allafah qulubuhumÂ not get the zakat, which none of the companions who opposed it. So opinionsÂ of Umar is a statute (ijmaâ€™) of the Companions and considered abrogatedpart muâ€™allaf. This paper studies about The reason of Umar bin Khattab didÂ not provide the right of zakat to the muâ€™allaf as mustahiq of zakat, and howÂ contemporary scholars put Umar thoughts about abortion right of muâ€™allafÂ as mustahiq of zakat in fiqh science literatures. The results of this researchÂ are, First, Umar bin Khattab abort asnaf rights for â€œal-muâ€™allafah qulubuhumâ€Â as a recipient of Zakat is due to the existence of a â€˜illat (the reasons behindÂ the solutions and decisions) that the state of â€œweak faithâ€. Second, the scienceÂ of fiqh repertory, contemporary scholars put the Umar thoughts as a basisÂ of ijtihad with the provision if the spirit of the background (â€˜illat law) is stillÂ visible, then the provisions of law applicable